Bio-ethanol production optimization using ACD with ESN critic - Iliev, V.; Kostov, G.; Stoycheva, J.; Koprinkova-Hristova, P.; Angelov, M.; Popova, S. (2011 International Symposium on Innovations in Intelligent Systems and Applications, 2011)
In the present paper on-line action-dependent heuristic neuro-dynamic programming was applied for optimization of a complex nonlinear production process. The approach is based on recurrent neural network architecture - Echo state network (ESN) - as critic network within the frame of adaptive critic design (ACD) scheme. The subject for optimization is bio-ethanol fermentation. The aim was to increase process productivity defining optimal dilution rate profile. The obtained by simulations results are good basis for further experimental investigations.